India’s foreign policy towards Central and Eastern Europe in 2014-2019 - Dahl, Michał (Przegląd Wschodnioeuropejski, 2021)
It has been said that Central and Eastern Europe can be seen as an interesting direction for Indian political and economic expansion. Both the data on diplomatic activity and India’s trade with the countries of CEE, however, prove that the region is not of key importance for New Delhi’s foreign policy. On the other hand, a steadily growing trade turnover allows assuming that the current situation will gradually change. The conclusions may be confirmed by the analysis of New Delhi’s diplomacy directions in the region. The Indian leaders (not the most important figures, taking into account symbolism and real significance) visited in the years 2014-2019 the CEE countries with the highest trade turnover with India, namely Poland, the Czech Republic, Hungary and Romania. They also paid visits to Bulgaria, Croatia and Serbia, that is countries with which India’s trade turnover is relatively low, but steadily growing. It may indicate a desire to establish more active diplomatic and economic involvement in this region than previously.